2003
DOI: 10.1046/j.1445-5994.2003.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines: perspectives of clinicians in Queensland public hospitals

Abstract: In general, clinicians working in public hospitals use CPG and view them positively. Based on free-text comments, a minority of non-medical respondents perceived guidelines and pathways as interchangeable tools. Improved uptake is dependent on increasing access, enhancing user-friendly guideline presentation, deploying local opinion leaders, and mitigating environmental barriers to implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
5
24
1
1
Order By: Relevance
“…This finding is of concern but is consistent with one previous study of physiotherapists [30] yet lower than that reported in another study of physiotherapists (over 90% used clinical practice guidelines) [34], lower than a study of allied health professionals (75% used clinical practice guidelines) [36], and lower than a study of health professionals in public hospitals (about 66% used clinical practice guidelines) [43]. The respondents in our study were significantly more likely to use clinical practice guidelines when they perceived that EBP assisted in decisions about patient care.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is of concern but is consistent with one previous study of physiotherapists [30] yet lower than that reported in another study of physiotherapists (over 90% used clinical practice guidelines) [34], lower than a study of allied health professionals (75% used clinical practice guidelines) [36], and lower than a study of health professionals in public hospitals (about 66% used clinical practice guidelines) [43]. The respondents in our study were significantly more likely to use clinical practice guidelines when they perceived that EBP assisted in decisions about patient care.…”
Section: Discussionsupporting
confidence: 87%
“…[42][43][44] Lack of time to stay informed about guidelines has also been identified elsewhere as an important barrier to adherence. [45][46][47] Consistent with previous data, the perception that guidelines can increase malpractice liability was held by a substantial number of the respondents. 44,48 As in other studies that compared the attitudes toward practice guidelines among nurses and physicians, 35,[49][50][51][52] nurses and other healthcare professionals in this study reported more positive attitudes than physicians did, and those working in pediatric ICUs were more likely to have more positive attitude scores than were those employed in other types of ICUs.…”
Section: Discussionsupporting
confidence: 84%
“…studies have demonstrated practice variation in the management of cellulitis 18,19 and have called for practice guidelines. 19,20 The Eron/Passos 6,7 classification system was not a useful discriminator of length of stay in our patient population. When applied to our cohort, most of our patients were Class II.…”
Section: Discussionmentioning
confidence: 89%